Antioxidant Effects of Caffeic Acid Lead to Protection of Drosophila Intestinal Stem Cell Aging - Sheng, Xiao; Zhu, Yuedan; Zhou, Juanyu; Yan, La; Du, Gang; Liu, Zhiming; Chen, Haiyang (Frontiers in Cell and Developmental Biology, 2021)
The dysfunction or exhaustion of adult stem cells during aging is closely linked to tissue aging and age-related diseases. Circumventing this aging-related exhaustion of adult stem cells could significantly alleviate the functional decline of organs. Therefore, identifying small molecular compounds that could prevent the age-related decline of stem cell function is a primary goal in anti-aging research. Caffeic acid (CA), a phenolic compound synthesized in plants, offers substantial health benefits for multiple age-related diseases and aging. However, the effects of CA on adult stem cells remain largely unknown. Using the Drosophila midgut as a model, this study showed that oral administration with CA significantly delayed age-associated Drosophila gut dysplasia caused by the dysregulation of intestinal stem cells (ISCs) upon aging. Moreover, administering CA retarded the decline of intestinal functions in aged Drosophila and prevented hyperproliferation of age-associated ISC by suppressing oxidative stress-associated JNK signaling. On the other hand, CA supplementation significantly ameliorated the gut hyperplasia defect and reduced environmentally-induced mortality, revealing the positive effects of CA on tolerance to stress responses. Taken together, our findings report a crucial role of CA in delaying age-related changes in intestinal stem cells of Drosophila.